Knowledge Of Students Of Senior Highs School 2 Bulukumba About Free Sex - Sumarni Sumarni; Erniawati Erniawati; Nuraeni Nuraeni; Jusni Jusni; Sri Ningsih (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2019)
Promiscuity in the era of globalization is increasingly worrying. The pace of technological progress at this time turns out to have many impacts on the global community, especially in terms of educators. Research to find out students about sexual behavior at SMA Negeri 2 Bulukumba this research is a quantitative research. The research subjects were 70 students at SMAN 2 Bulukumba who were taken by total sampling. Data collection using cakeisitioner. The results showed that the level of students about free sex behavior was at a good level.